Pemikiran Politik Islam di Indonesia - Khoirul Huda; Muhammad Naufal Ihsan (AHKAM, 2026)
Although Islamic political thought in Indonesia has received attention in various studies, studies that specifically analyze the relationship between Islam and nationalism within the framework of Islamic political thought remain limited. This study aims to analyze the meaning of Islamic political thought as a conceptual effort by Muslims to formulate a system of power that is aligned with sharia values and the national context. This study used a qualitative method with a library research design and historical and normative approaches. Data sources consisted of primary and secondary data collected through documentation study by reading, understanding, examining, and recording various relevant literature, then analyzed using a descriptive-analytical method. The results show that Islamic political theory and thought in Indonesia have undergone transformation from the colonial period, the independence movement, to the reform era, reflecting adaptation to changing times. In the context of the relationship between Islam and nationalism, there has been a struggle between religious identity and national commitment that has produced a synthesis in the form of the Pancasila state. In addition, Islamic political thought in Indonesia has developed into several main schools, namely formalistic, substantive, and transformative, each with different characteristics and orientations. This study affirms that Islamic political thought in Indonesia is dynamic, contextual, and continues to develop in response to the challenges of the times. The implications of this study include theoretical contributions to the development of Islamic political thought literature and practical contributions for educators, students, historians, and researchers in understanding the dynamics of the relationship between Islam, nationalism, and national politics in Indonesia.